Impact of State Participation in Share Capital on Performance of Companies in Capital Emerging Markets - Виктория Артуровна Черкасова (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2014)
The review is constructed on financial architecture, which is one of the most popular concepts of the corporate finance. There is a limited number of the empirical works devoted to studying of the state participation in a share capital, hence, the article contains the review of the theoretical works devoted both to influence of structure of the ownership on results of activity of the company, and to features of the state participation in the capital of the companies. The comparative analysis of degree of this influence for the different countries is carried out.